A letter to the editors: Introducing The Examination and The Letter. Issue 1 (1st September 2020) - Lyons, William
Irish-Australian philosopher William Lyons is the author of the short films The Examination and The Letter. These are cinematographic manifestations of the author's enterprise in communicating philosophical ideas beyond the formal conventions of professional philosophy. The present entry consists of an endearing and informative letter that Lyons enclosed with the films when he sent them to the editors of Empedocles: European Journal for the Philosophy of Communication upon their request. It is reproduced here verbatim as a preamble to the discussion about them that follows in this same issue.